PELAKSANAAN GOOD GOVERNANCE PADA PROGRAM GRAND STRATEGI DALAM MEWUJUDKAN KOTA TRANSIT DAN PETROPOLITAN DI KECAMATAN PINGGIR KABUPATEN BENGKALIS, 2010-2015 - Yuni Sara Silaban; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research do to describe implementation preparation grand strategy program in Pinggir subdistrict as transit and petropolitan city. From the set of target program’s grand strategy has a span of five years, between years 2010-2015. But the expected this program will not finish up, until any given year, this program is still in the preparation stage is the preparation of the planning and preparation of the complate document infrastructure facilities to support the realization Pinggir subdistrict as Transit and Petropolitan city.In theory Good Governance there are six into factors that affect the implementation, namely: basic measures and objectives, resources, communication between the organization and activities of the implementing body characteristics implementers, economic condition, social and political as well as the tendency executor. The method used in this study is a qualitative.Based on research conducted by on the concept of the implementation preparation grand strategy program Pinggir subdistrict as transit and petropolitan city. Until now final period of predetermined targets, the preparation of the program is assessed not maximized, only until the completencess documents, and from 12 programs, only 60 % realized. As for infrastructurefacilities only reached the stage of rolling road which when seen today still done.Keywords :Grand strategy, transit and petropolitan, implementation, preparation.